Islamic Education Design in the Face of the Society Era 5.0: A Literature Review Approach: Desain Pendidikan Islam dalam Menghadapi Era Society 5.0: Pendekatan Kajian Literatur - Hilmi, Fuad; Maryana, Ina (Journal of Society and Development, 2025)
The integration of technology in education in the era of Society 5.0, by highlighting the challenges and opportunities faced by educators and students. Educators are required to not only master the teaching material, but also be able to adapt to technological developments to increase learning effectiveness. Various digital platforms, such as Quizziz and Google Forms, can be leveraged in learning evaluation, while artificial intelligence (AI) needs to be used to ensure the accuracy of information. In addition, social media has great potential as an educational tool, where teachers can take advantage of digital trends to build students' critical thinking and instill awareness of the importance of information verification. In the context of Islamic education, the integration between religious science and science is a challenge that needs to be overcome in order to create a holistic education. The takhrij method in hadith discourse can be used as a model in verifying information spread on the internet, so that students can be more selective in receiving information. More broadly, Society 5.0 has the potential to create a super smart society by utilizing technological innovations to improve the quality of education. With a learning approach that combines technology and Islamic educational values, it is hoped that the education system can produce students who are not only academically intelligent, but also have a strong character and are responsible in the use of technology. Through this strategy, education can be the main instrument in building an adaptive, innovative, and ethical society in facing the digital era.